Text as a Means of Forming Intercultural Communication in Language Education - Tatiana A. Volkova (Polylinguality and Transcultural Practices)
In the study one of the important problems of the methodology of teaching languages is considered - the formation of intercultural communication. Since the Republic of Mari El is multinational, multicultural, issues of language education are particularly relevant. In this article the analyze of the role of texts in the modern intercultural concept of teaching languages in the educational process is performed. The close connection between language and culture is emphasized, while it is noted that the differences between representatives of different ethnic groups, manifested not only at the level of knowledge/ignorance of the language, but also in other areas, can be overcome by penetrating into the culture of the people. This is not only about teaching foreign languages, but also about teaching the Russian language in the context of multiculturalism and multilingualism, which are most clearly manifested at present in the republic. Particular attention is paid to referring to texts of various types, functional styles when studying the discipline “Russian language and culture of speech”. The article describes ways of referring to the text when studying the topics “Literary norms of the Russian language”, “Functional styles“, “Culture of oral and written business communication”, “Speech etiquette. Ethics of speech communication”, “Stages of preparation and conducting public speeches”, “Culture of discussion and controversy”.